ABOUT INTERDISCIPLINARITY AS A CONCEPT - Costa, Danilo da; Gonçalves, João Carlos; Cantino, Roberta Cristina Gonçalves; Moura, Rosilene da Silva (Revista Coleta Científica, 2021)
In today’s culture, interdisciplinarity is seen as a necessary prerequisite for teaching and research. The concept of interdisciplinarity has recently gained traction in policy, practice, teaching and research circles. While there is still some skepticism about the concept, it has recently taken on moral connotations with explanations of why interdisciplinarity is desirable and inevitable. As a result, both the Academy of Higher Education and the Research Councils support interdisciplinarity in both teaching and research. Based solely on an exhaustive review of the literature, this article provides an outline of the idea, its teaching implications, and its meaning for contemporary policy. The idea of interdisciplinarity, on the other hand, has been exaggerated to the point of trivialization. The topic is timely, interesting and little known in practice, so it needs to be considered in depth. Transformations, deconstructions and reconstructions of what is typically presented are necessary to adhere to an interdisciplinary project. The study of interdisciplinarity is still in its infancy, not offering theoretical and methodological security for those who feel attracted to develop a work of this magnitude.